2018
DOI: 10.1080/08977194.2018.1473393
|View full text |Cite
|
Sign up to set email alerts
|

STAT3: a multifaceted oncoprotein

Abstract: Signal transducer and activator of transcription (STAT) 3 is a key signalling protein engaged by a multitude of growth factors and cytokines to elicit diverse biological outcomes including cellular growth, differentiation, and survival. The complete loss of STAT3 is not compatible with life and even partial loss of function mutations lead to debilitating pathologies like hyper IgE syndrome. Conversely, augmented STAT3 activity has been reported in as many as 50% of all human tumours. The dogma of STAT3 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 126 publications
2
108
0
Order By: Relevance
“…IL-6 and IL-23 induce Th17 cell differentiation through activation of the STAT3 signaling (Korn et al, 2009;Dong, 2008). Moreover, the phosphorylation of STAT3 (phospho-STAT3) at Y705 residue is known to be required for Th17 cell differentiation (Guanizo et al, 2018;Renner et al, 2008). Interestingly, the nuclear dimeric PKM2 form can act as a protein kinase and phosphorylate STAT3 at Y705 in the nucleus, enhancing its transcriptional activity and promoting tumor growth (Gao et al, 2012).…”
Section: Pkm2 Promotes Stat3 Phosphorylation In Th17 Cellsmentioning
confidence: 99%
“…IL-6 and IL-23 induce Th17 cell differentiation through activation of the STAT3 signaling (Korn et al, 2009;Dong, 2008). Moreover, the phosphorylation of STAT3 (phospho-STAT3) at Y705 residue is known to be required for Th17 cell differentiation (Guanizo et al, 2018;Renner et al, 2008). Interestingly, the nuclear dimeric PKM2 form can act as a protein kinase and phosphorylate STAT3 at Y705 in the nucleus, enhancing its transcriptional activity and promoting tumor growth (Gao et al, 2012).…”
Section: Pkm2 Promotes Stat3 Phosphorylation In Th17 Cellsmentioning
confidence: 99%
“…We used peritoneal exudate cells (PECs) for these studies because of the known requirement for STAT3 in growth factor signalling and differentiation (e.g. CSF-1, GM-CSF pathways) 28 , moreover, PECs represent the local immunological environment, consisting predominately of myeloid cells 29 . We found that STAT3 SA PECs have a significant defect in both resting glycolysis and the early glycolytic burst observed in wild-type macrophages following LPS-challenge as determined by assaying the extracellular acidification rate (ECAR) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an important transducer of many cytokines and growth factors, STAT proteins have 7 members (STAT1, STAT2, STAT3, STAT4, STAT5A, STAT5B and STAT6), and STAT3 is the most widely known and researched [28]. Compared with normal tissues, STAT3 is overexpressed or constitutively activated in about 70% of human solid tumors and in 94% of ovarian cancers [19,[29][30][31]. .…”
Section: Discussionmentioning
confidence: 99%